Potential of interseeded soybean and grain sorghum as a forage for dairy cattle - John E. Shirley; J. Koger (Kansas Agricultural Experiment Station Research Reports, 1985)
Soybeans interseeded with grain sorghum (soy-sorghum) was compared to corn silage as a silage crop for ruminant animals over a 3-year period. Results indicate that DM yields are comparable if soy-sorghum is seeded early (June 6) but less than corn silage when seeded late (June 28). Liquid manure may be substituted for commercial fertilizer without a significant decrease in soy-sorghum DM yield per acre.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Soybean; Grain sorghum; Dry matter; Total digestible nutrients (TDN); Crude protein